Numerical simulation of isolation of cancer cells in a microfluidic chip. (22nd July 2015) - Djukic, T; Topalovic, M; Filipovic, N
Abstract: Cancer is a disease that is characterized by the uncontrolled increase of numbers of cells. Circulating tumour cells (CTCs) are separated from the primary tumor, circulate in the bloodstream and form metastases. Circulating tumor cells can be identified in the blood of a patient by taking a blood sample. Microfluidic chips are a new technique that is used to isolate these cells from the blood sample. In this paper a numerical model is presented that is able to simulate the motion of individual cells through a microfluidic chip. The proposed numerical model gives very valuable insight into the processes happening within a microfluidic chip. The accuracy of the proposed model is compared with experimental results. The experimental setup that is described in literature is used to create identical geometrical domains and define simulation parameters. A good agreement of experimental and numerical results demonstrates that the proposed model can be successfully used to simulate complex behaviour of CTCs inside microfluidic chips.